"Civilizing" the Colonial Subject: The Co-Evolution of State and Slavery in South Carolina, 1670–1739. (25th June 2015) - Unknown
Abstract: South Carolina was a staggeringly weak polity from its founding in 1670 until the 1730s. Nevertheless, in that time, and while facing significant opposition from powerful indigenous neighbors, the colony constructed a robust plantation system that boasted the highest slave-to-freeman ratio in mainland North America. Taking this fact as a point of departure, I examine the early management of unfree labor in South Carolina as an exemplary moment of settler-colonial state formation. Departing from the treatment of state formation as a process of centralizing "legitimate violence, " I investigate how the colonial state, and in particular the Commons House of Assembly, asserted an exclusive claim to authority by monopolizing the question of legitimacy itself. In managing unfree laborers, the colonial state extended its authority over supposedly private relations between master and slave and increasingly recast slavery in racial terms. This recasting of racial slavery rested, I argue, on a distinction, pervasive throughout English North America, which divided the world into spheres of savagery and civility. Beneath the racial reordering of colonial life, the institution of slavery was rooted in the same ideological distinction by which the colonial state's claims to authority were justified, with the putative "savagery" of the slave or of the Indian being counterpoised to the supposed civility of English settlers. This article contributes to the literatures on Atlantic slavery and American colonial history, and invites comparison with accounts of state formation and settler colonialism beyond Anglo-America.